Balancing the Risk of Complications in Foot and Ankle Surgical Patients Taking Antithrombotic Medication. Issue 6 (December 2014) - Miller, Steven; Nitzki-George, Diane; Caprini, Joseph A.
This review intends to provide guidance regarding perioperative management of anticoagulation and antiplatelet drug therapy as they relate to foot and ankle surgery. Venous and arterial thromboembolism are conditions in which the blood clots inappropriately, causing considerable morbidity and mortality. With an increase in awareness of thromboembolic risk factors and expansion of therapeutic options, more patients are routinely taking antithrombotic medication. When these patients require invasive procedures, a decision needs to be made if antithrombotic medication should be held perioperatively and if additional precautions are needed in the interim. Understanding the factors affecting the management of thromboembolism during the perioperative period can reduce the potential for complications. Levels of Evidence: Therapeutic, Level V: Expert opinion